Meningkatkan Kualitas dan Kreativitas Belajar Melalui Program Bimbingan Belajar Berbasis Joyfull Learning di Masa Pandemi - Marwiyah, Syarifatul; Dasuki, Mohammad; Fitria, Hanifatul (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2023)
This tutoring activity is a service motivated by the many learning problems experienced by students due to online learning during the pandemic which was carried out at home. Some of the obstacles are the lack of knowledge of parents about material, technology, and assisting their children. In addition, children's interest in learning is reduced, it is difficult to operate technology, and learning facilities are inadequate. Then service through tutoring is carried out with the aim of improving the quality and creativity of children's learning. The implementation method is carried out in several stages, namely the exploration, create and action, evaluation, report and dessimination stages. The results of this dedication prove that Joyful Learning-based tutoring helps students who initially have low interest in learning because the quality of learning is not good, after participating in tutoring the quality and creativity of children's learning is maximized.